THE PHENOMENON OF AESTHETICAL ANTROPLOGY IN KONTEST OF DEVELOPMENT OF THE UKRAINIAN POETIC CINEMA - Pichenikova, S. G. (Anthropological Measurements of Philosophical Research, 2012)
Becoming of modern philosophical space takes a place in the aspect of interdiscipline approach. As a result of co-operating of philosophy with many humanities, new directions of modern philosophical idea appear. Aesthetical anthropology is one of concepts of modern scientific knowledge which presents the theories of new type. In the structure of the poetic cinema aesthetical anthropology will be realized foremost in an author idea, and also by interpretation of cultural sense initiator through the prism of spectator. A question of development of the cinema art in the context of aesthetical anthropology, is actual and from a practical side represent «plural» and «many» approaches, in relation to the problems of self - development and self-knowledge of a man.